VD_FINDINFO HC / 2012 / 632 vom 2. Oktober 2012 - VD Tribunal cantonal (2012)
AVOCAT D'OFFICE, INDEMNITÉEN GÉNÉRAL, HONORAIRES | 110 CPC (CH), 122 al. 1 let. a CPC (CH), 319 let. b ch. 1 CPC (CH), 320 CPC (CH), 322 al. 1 CPC (CH), 2 al. 1 RAJ